Efektivitas dan Efisiensi Sistem Manajemen Hauling Teman Indobara dalam Kerangka Pengembangan dan Pemberdayaan Masyarakat Pada PT. XYZ - Mangihut Bernard Sinaga; Tomi Oktavianor (JURNAL BISNIS DAN PEMBANGUNAN, 2025)
Abstract: This research aims to determine the effectiveness and efficiency of Teman Indobara's Hauling Management System (SMH) within the framework of Community Development and Empowerment (PPM) at PT XYZ. This research uses a qualitative approach with a research focus on identifying and analyzing factors that affect the effectiveness and efficiency of Teman Indobara's SMH in 3 components, namely related to production achievement, fuel consumption, and coal cargo loss at PT XYZ. The research data was collected through the process of interviews, surveys, observations, documentation studies of primary and secondary data of PT XYZ, and analyzed using the Creswell (2014) model. The results showed that after the use of SMH Teman Indobara, there was an increase in the quality of supervision from the operational, safety, and security aspects of coal coal hauling process from the mine ROM area to the port. In addition, it also has a positive impact on the community around the mine within the framework of PT XYZ's PPM in the real economy sector. So that with the implementation of SMH from 2021 to 2023, it can be seen that there is an increase in coal hauling achievements by 62%, fuel ratio efficiency of 0.004 liters per ton per kilometer, and can be known earlier the indications of coal cargo loss (theft). The coal hauling achievement provides benefits for BUMDES hauling partners for increasing revenue of 109%.